Grammar Teaching Approach in Secondary School English Textbooks - Ting, Su Hie; Musa, Muriatul Khusmah; Siew, Lan Tan (2010)
The study examined the grammar teaching approach in textbooks used for teaching English for Forms 1 to 5 in Sarawak. The specific objectives of the study were to determine whether the grammar presentation approach was mainly inductive or deductive, and the extent of accuracy- and meaningfocussed grammar practice. The Form 1 to Form 5 English textbooks prescribed for Sarawak secondary schools by the Ministry of Education were analysed by unit to find out how the teaching of grammar is contextualised within the learning units. The framework for the analysis was the shallow-end form ofthe Communicative Approach which underpins the KBSM English curriculum. The results ofthe study showed that the English textbooks tended towards the deductive approach for the teaching of grammar and the grammar practice was more accuracy-based than meaning-based. The results suggested that a stronger theme for the teaching-learning units may facilitate use of the grammatical structures for meaningful communication